Phenotypic Characterization of Some Durum Wheat (Triticum durum Desf.) Genotypes Growing under Semi-Arid Conditions - Ali, Guendouz; Abderrahmane, Hannachi; Abidine, Fellahi Zine El; Frih, Benalia (International Journal of Bio-resource and Stress Management, 2021)
Breeders are permanently looking for an efficient method of developing genotypes with improved yield. The aim of this study was to evaluate the performance of some durum wheat genotypes, the study of the correlations between traits and the direct effect of each trait on final grain yield. Twenty genotypes of durum wheat (Triticum durum Desf.) were planted in the experimental fields of INRAA, Setif, Algeria in (2016 –2017) crop season. The genotypes tested were grown in a randomized block design with three replications. The analyses of variance (ANOVA) demonstrate the existence of genetic diversity between genotypes tested. In addition, significant and positive correlations were registered between grain yield (GY) and days to heading (DH), number of spikes per square meter (NSM) and number of kernels per spike (NKS). The path analysis (PA) demonstrates positive and significant direct effects of the number of spikes per square meter (NSM), thousand kernels weight (TKW) and number of kernels per spike (NKS) on grain yield. Overall, the results proved that the genotypes Rezzak, Ofanto and BIDI 17 have the best ranking with the highest grain yield, and these can be recommended as the best genotypes for some in this area. In addition, the Principal Component Analysis (PCA) proved that the genotypes Rezzak, Bidi17, Ofanto, Kebir and Adnan 2 are very suitable genotypes for growing under semi-arid conditions.